Omega-3 polyunsatured fatty acids and physical performance across the lifespan: a narrative review - Azzolino, Domenico; Bertoni, Camilla; De Cosmi, Valentina; Spolidoro, Giulia Carla Immacolata; Agostoni, Carlo; Lucchi, Tiziano; Mazzocchi, Alessandra (Frontiers in Nutrition, 2024)
Background & Aims Physical performance is a major contributor of mobility and independence during older life. Despite a progressive decline in musculoskeletal function starts from middle age, several factors acting during the life-course can negatively influence musculoskeletal functional capacities. Lifestyle interventions incorporating nutrition and physical exercise can help maximizing the muscle functional capacities in early life as well as preserving them later in life. Among various dietary compounds, omega-3 polyunsaturated fatty acids (PUFAs) are gaining growing attention for their potential effects on muscle membrane composition and muscle function. Indeed, several pathways are enhanced, such as an attenuation of pro-inflammatory oxidative stress, mitochondrial function, activation of the mammalian target of rapamycin (mTOR) signaling and reduction of insulin resistance. Methods We performed a narrative review to explore the existing literature on the relationship between omega-3 PUFAs and physical performance across the life-course. Results Growing evidence from randomized controlled trials (RCTs) suggests beneficial effects of omega-3 PUFAs on muscle function, including physical performance parameters in mid to later life. On the other hand, despite a direct association in early life is not available in literature, some mechanisms by which omega-3 PUFAs may contribute to improved adult physical performance could be hypothesized. Conclusion Omega-3 PUFAs are gaining growing attention for their positive effect on muscle function parameters. The integration of physical function measures in future studies would be of great interest to explore whether omega-3 PUFAs could contribute to improved muscle function, starting from early life and extending throughout the lifespan. However, larger and high-quality RCTs are needed to fully elucidate the beneficial effects of omega-3 PUFAs supplementation on muscle mass and function.